A study on social enterprises in Singapore : the effectiveness of social media in generating purchase intention and brand loyalty. - Toh, Ling Hui. (2012)
The purpose of this research study is to investigate various ways social enterprises can utilize social media to create better awareness of their products and/or services with a view to increase purchase intentions and brand loyalty of consumers. The key objectives of this study include determining which specific sales promotional tools and advertisement appeals are most effective in positively influencing consumers’ purchase intentions and brand loyalty. It is hoped that this study will serve as a guide for social enterprises to utilise social media tools more effectively, enabling them to engage their target market effectively. Moreover, this study will be a valuable addition towards the existing limited literature on social enterprises, especially in Singapore.